EFEKTIVITAS LAYANAN KONSELING KELOMPOK DENGAN PENDEKATAN COGNITIVE BEHAVIOR THERAPHY (CBT) UNTUK MENINGKATKAN SELF EFFYCACY PADA SISWA SMK PEMBANGUNAN NASIONAL DI BEKASI TAHUN AJARAN 2019/2020 - Eka Safriliani; Enci Zarkasih; Yusuf Maulana (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2020)
This study aims to determine the effectiveness of group counseling services with a cognitive behavior therapy (CBT) approach to improve self-efficacy in National Development Vocational High School (SMK) students. This type of research uses pre-experimental design with one group pre-posttest design. The number of subjects used in this study were 8 students of class X TKR (Light Vehicle Engineering). The sampling technique using purposive sampling. Data collection used self-efficacy questionnaire. Data analysis method used is the Paired t Test to test the comparative hypothesis of the average of two samples and find out whether there are differences before and after treatment. The results of the analysis showed a t value of -8.729 with Sig. (2-tailed) = 0,000 (Sig. (2-tailed) <0.05) then H0 is rejected and H1 is accepted so that the conclusions of the results of this study indicate that: group counseling services with cognitive behavior therapy (CBT) approaches are effective for improving self -Efficacy of class X students of the National Development Vocational School.